“It is much more real when it comes from them”: The role of experts by experience in the integration of mental health nursing theory and practice - Happell, Brenda; Waks, Shifra; Horgan, Aine; Greaney, Sonya; Manning, Fionnuala; Goodwin, John; Bocking, Julia; Scholz, Brett; Hals, Elisabeth; Granerud, Arild; Doody, Rory; Platania‐Phung, Chris; et al. (Perspectives in psychiatric care, 2020)
Purpose To examine nursing students' perceptions of Experts by Experience impact on theoretical and practical learning. Design and Methods Qualitative exploratory study involving focus groups with undergraduate nursing students from five European countries and Australia. Data were analyzed thematically. Findings Participants described positive impacts as: bridging the theory and practice gap through first‐hand experience, including sub‐themes: bringing theory to life; can't be taught any other way, and innovative teaching methods fueling curiosity. Relevance to Clinical Practice Integrating theory and practice is key for quality mental health nursing practice. Experts by experience can potentially contribute to reducing this enduring gap.